Effect Of Fruit And Cork Extract Of Ficus Lacor Buch Ham On α/β -Glucosidase, α -Amylase, Lipase, Glucose Absorption And Uptake: Pharmaceutical Science-Antidiabetic Activity of Ficus Lacor Buch - Mule V. S; Naikwade N. S (International Journal of Life Science and Pharma Research, 2022)
Fruits of the plant Ficus Lacor Buch. Ham. were used traditionally for treatment of diabetes mellitus. The present study was undertaken to evaluate the antidiabetic potential of the plant using in vitro approach. Effect of Ficus Lacor Buch. Ham. was evaluated using α/β -glucosidase, α-amylase and lipase enzyme inhibition assay methods. The glucose absorption in intestine was evaluated using everted rat jejunum while glucose uptake was evaluated using isolated rat hemidiaphragm. Fruit and cork ethanolic extract was prepared by using soxhlation extraction method. In vitro assay of α-glucosidase showed that IC50 value of fruit extract was 83.03 µg/ml and cork extract 88.32 µg/ml when compared with control group acarbose. β-glucosidase enzyme was inhibited by fruit and cork extract of plant with IC50 value of fruit and cork extract 132.71 µg/ml and 171.93 µg/ml. The extracts further quantify α-amylase inhibitory activity of fruit (IC50 77.93 µg/ml) and cork (IC50 111.94 µg/ml) extract. Lipase inhibitory assay indicated the effect of plant extract on lipase enzyme was not prominent when compared to orlistat. Absorption of glucose through everted rat jejunum was reduced significantly (P ? 0.05) when compared with standard metformin. Effect of fruit and cork extract on rat hemidiaphragm exhibited significant (P ? 0.05) increase in glucose uptake when compared with standard metformin. Result suggests Ficus Lacor Buch. Ham. is effective in inhibiting carbohydrate metabolizing enzymes α/β –glucosidase and α-amylase while lipase enzyme was not affected. Fruit and cork extract of the plant was found to reduce significantly glucose absorption in everted rat jejunum. The significant increase in glucose uptake was observed in isolated rat diaphragm. The result reveals that Ficus Lacor Buch. Ham. acts by inhibiting carbohydrate metabolizing enzymes, reducing glucose absorption in intestine and increasing glucose uptake in hemidiaphragm.